2010
DOI: 10.1111/j.1365-2753.2009.01203.x
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate‐associated osteonecrosis of the jaw. Knowledge and attitudes of dentists and dental students: a preliminary study

Abstract: Training strategies need to be established as regards bisphosphonate-associated ONJ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
24
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 23 publications
(65 reference statements)
5
24
0
5
Order By: Relevance
“…With the purpose of identifying which patients had a greater risk of BRONJ, it has been proposed the usefulness of determining serum CTX (telomere C-terminal of collagen 1), a biologic index to measure bone remodeling and bone resorption, pointing out that those patients who had taken oral BPs for more than 3 years and who had CTX below 150 pg/ml would be at greater risk of developing BRONJ during dental surgery (22,35). Kwon et al (36) correlated the staging of osteonecrosis with serum CTX in 18 osteoporotic patients receiving oral BPs treatment, the authors found a significant correlation between the disease severity and the risk assessment using serum CTX.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the purpose of identifying which patients had a greater risk of BRONJ, it has been proposed the usefulness of determining serum CTX (telomere C-terminal of collagen 1), a biologic index to measure bone remodeling and bone resorption, pointing out that those patients who had taken oral BPs for more than 3 years and who had CTX below 150 pg/ml would be at greater risk of developing BRONJ during dental surgery (22,35). Kwon et al (36) correlated the staging of osteonecrosis with serum CTX in 18 osteoporotic patients receiving oral BPs treatment, the authors found a significant correlation between the disease severity and the risk assessment using serum CTX.…”
Section: Methodsmentioning
confidence: 99%
“…Lópes-Jornet et al (35), Migliorati et al (15) and Bauer et al (3) observed that in all groups only a minority knew adequate information concerning the use of BPs, suggesting that greater educational efforts should be made to promote knowledge of this pathology at both undergraduate and postgraduate levels, and that the majority of the patients receiving oral or IV BPs are not adequately informed about possible adverse effects of their BP therapy. Table 1 shows the most important topics related to AONJ.…”
Section: Methodsmentioning
confidence: 99%
“…Khan et al recalled that this complication is rare and reported a cumulative incidence of 0.001% in Ontario for osteoporosis or metabolic bone disease observations 21 . This side effect is not always recognised by dentists 22 . De Lima et al found that 58% of Brazilian dentists did not recognise BP-related ONJ (BRONJ) as an oral side effect of BP or point out oral conditions that are not associated with the use of BP 23 .…”
Section: Discussionmentioning
confidence: 98%
“…recalled that this complication is rare and reported a cumulative incidence of 0.001% in Ontario for osteoporosis or metabolic bone disease observations. This side effect is not always recognised by dentists. De Lima et al .…”
Section: Discussionmentioning
confidence: 99%
“…• Lack and/or inadequate knowledge of BRONJ-related issues. A recent report (Lopez-Jornet et al, 2010) highlights that there are dental professionals who are not informed yet, or at least not adequately informed, as regards BRONJ and the management of patients taking bisphosphonates; of course, this is a breach of the duty of the prudent practitioner to remain current with scientific evidence.…”
mentioning
confidence: 99%